Suppression of Microgliosis With the Colony-Stimulating Factor 1 Receptor Inhibitor PLX3397 Does Not Attenuate Memory Defects During Epileptogenesis in the Rat - Wyatt-Johnson, Season K.; Sommer, Alexandra L.; Shim, Kevin Y.; Brewster, Amy L. (Frontiers in Neurology, 2021)
Events of status epilepticus (SE) trigger the development of temporal lobe epilepsy (TLE), a type of focal epilepsy that is commonly drug-resistant and is highly comorbid with cognitive deficits. While SE-induced hippocampal injury, accompanied by gliosis and neuronal loss, typically disrupts cognitive functions resulting in memory defects, it is not definitively known how. Our previous studies revealed extensive hippocampal microgliosis that peaked between 2-3 weeks after SE and paralleled the development of cognitive impairments, suggesting a role for reactive microglia in this pathophysiology. Microglial survival and proliferation are regulated by the colony-stimulating factor 1 receptor (CSF1R). The CSF1R inhibitor PLX3397 has been shown to reduce/deplete microglial populations and improve cognitive performance in models of neurodegenerative disorders. Therefore, we hypothesized that suppression of microgliosis with PLX3397 during epileptogenesis may attenuate the hippocampal-dependent spatial learning and memory deficits in the rat pilocarpine model of SE and acquired TLE. Different groups of control and SE rats were fed standard chow (SC) or chow with PLX3397 starting immediately after SE and for 3 weeks. Novel object recognition (NOR) and Barnes maze (BM) were performed to determine memory function between 2-3 weeks after SE. Then microglial populations were assessed using immunohistochemistry. Control rats fed with either SC or PLX3397 performed similarly in both NOR and BM tests, differentiating novel vs. familiar objects in NOR, and rapidly learning the location of the hidden platform in BM. In contrast, both SE groups (CS and PLX3397) showed significant deficits in both NOR and BM tests compared to controls. Both PLX3397-treated control and SE groups had significantly decreased numbers of microglia in the hippocampus (60%) compared to those in SC. In parallel, we found that PLX3397 treatment also reduced SE-induced hippocampal astrogliosis. Thus, despite drastic reductions in microglial cells, memory was unaffected in the PLX3397-treated groups compared to those in CS, suggesting that remaining microglia may be sufficient to help maintain hippocampal functions. In sum, PLX3397 did not improve or worsen the memory deficits in rats that sustained pilocarpine-induced SE. Further research is required to determine whether microglia play a role in cognitive decline during epileptogenesis.